Combining a High Dose of Metformin With the SIRT1 Activator, SRT1720, Reduces Life Span in Aged Mice Fed a High-Fat Diet. (18th June 2020) - Palliyaguru, Dushani L; Minor, Robin K; Mitchell, Sarah J; Palacios, Hector H; Licata, Jordan J; Ward, Theresa M; Abulwerdi, Gelareh; Elliott, Peter; Westphal, Christoph; Ellis, James L; Sinclair, David A; Price, Nathan L; et al.
Abstract: SRT1720, a sirtuin1-activator, and metformin (MET), an antidiabetic drug, confer health and life-span benefits when administered individually. It is unclear whether combination of the two compounds could lead to additional benefits. Groups of 56-week-old C57BL/6J male mice were fed a high-fat diet (HFD) alone or supplemented with either SRT1720 (2 g/kg food), a high dose of MET (1% wt/wt food), or a combination of both. Animals were monitored for survival, body weight, food consumption, body composition, and rotarod performance. Mice treated with MET alone did not have improved longevity, and life span was dramatically reduced by combination of MET with SRT1720. Although all groups of animals were consuming similar amounts of food, mice on MET or MET + SRT1720 showed a sharp reduction in body weight. SRT1720 + MET mice also had lower percent body fat combined with better performance on the rotarod compared to controls. These data suggest that co-treatment of SRT1720 with MET is detrimental to survival at the doses used and, therefore, risk-benefits of combining life-span-extending drugs especially in older populations needs to be systematically evaluated.